MET dysregulation is a hallmark of aggressive disease in multiple myeloma patients. (23rd January 2014) - Rocci, Alberto; Gambella, Manuela; Aschero, Simona; Baldi, Ileana; Trusolino, Livio; Cavallo, Federica; Gay, Francesca; Larocca, Alessandra; Magarotto, Valeria; Omedè, Paola; Isaia, Gianluca; Bertotti, Andrea; et al.
Summary Abnormal activation of MET/HGF (Hepatocyte Growth Factor) pathway has been described in several tumours and increased HGF plasmatic levels have been detected in patients with aggressive multiple myeloma (MM). MET and HGF mRNA expression was investigated in 105 samples of purified plasma cells derived from newly diagnosed MM patients treated with bortezomib‐based induction therapy. Gene expression was compared with response to therapy and clinical outcome. MET gene copy number was also evaluated. MET mRNA expression was higher in CD138+ than in CD138− cells (median 76·90 vs. 11·24; P = 0·0009). Low MET mRNA expression characterized patients with better response (complete response or very good partial response) compared to other patients (median 56·10 vs. 134·83; P = 0·0006). After a median follow‐up of 50 months, patients with high MET mRNA expression displayed a worse progression‐free survival (PFS; P = 0·0029) and overall survival (OS; P = 0·0023) compared to those with low MET mRNA levels. Patients with both high MET mRNA expression and high β2‐microglobulin level (>5·5 mg/l) had further worse median PFS (P < 0·0001) and OS (P < 0·0001). Patients carrying 4 MET gene copies (8 out of 82, 9·8%) also had a short PFS. High MET mRNA expression identifies patients with dismal PFS and OS and the combination with high β2‐microglobulin further characterizes patients with worse outcome.